The Influence of the Utilization of the PLN Mobile Application on Customer Satisfaction in Ambon City - Vivi Varisa Achmad; Pieter Sammy Soselisa; Hengky Virgo Richardo Pattimukay (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to examine the effect of PLN Mobile application utilization on customer satisfaction in Ambon City, with a specific focus on user experiences in Poka Village as part of evaluating local-level e-Government implementation. Methodology: This study employed a quantitative associative approach using a structured questionnaire with a five-point Likert scale. Data were collected from 96 PLN Mobile users through purposive sampling. Statistical analysis was conducted using SPSS, including descriptive statistics, classical assumption tests, simple linear regression, t-test, and coefficient of determination analysis. Main Findings: The results indicate that PLN Mobile utilization has a significant and positive effect on customer satisfaction. Regression analysis shows a strong positive relationship between variables, with PLN Mobile utilization explaining 52% of the variance in customer satisfaction, confirming the effectiveness of digital public services. Novelty/Originality of this study: This study provides localized empirical evidence from eastern Indonesia, a region underrepresented in prior research. By focusing on community-level experiences in Ambon City, it enriches e-Government literature and offers practical insights for improving digital public service delivery in regional and developing contexts.